Impact of Tobacco Cessation Curriculum on Professional Competency of Dental Students: A Survey: Tobacco Cessation Curriculum on Professional Competency of Dental Students - Anzar, Wajiha; Askary, Syed Hussain; Taheer, Talal Bin; Bashir, Muhammad Bilal; Arshi, Sadaf; Zaidi, Syed Jaffar Abbas (Pakistan Journal of Health Sciences, 2025)
Tobacco cessation counseling (TCC) has become a crucial component in comprehensive patient care. Dentists are in a unique position to identify tobacco users due to regular patient contact and are pivotal in delivering TCC as part of comprehensive oral healthcare. Objectives: To assess the impact of the tobacco cessation curriculum on the professional competency and intention of dental students to provide TCC. Methods: An analytical cross-sectional study was conducted from January 2025 to March 2025. It involved students from clinical years, dental interns, and postgraduate students from all Public and Private Dental Colleges in Karachi who had a tobacco cessation curriculum in formal dental teaching. A structured, self-administered questionnaire was used to assess intentions and perceived barriers in TCC using constructs of the Theory of Planned Behaviour. Data were entered and analyzed using SPSS version 22.0. Frequencies and percentages were obtained for variables. The chi-square test was applied to evaluate associations. Results: The majority of participants, 239 (79.7%), demonstrated a high intention to deliver tobacco cessation counseling. No significant difference was observed in the intention of dental students and dentists to provide effective TCC (p-value>0.05). Statistically significant differences were observed between the barriers faced by dental students and dentists in that the students were more concerned that they lacked skills of TCC in comparison to dentists (p-value=0.04). Conclusions: The tobacco cessation curriculum effectively boosts dental students’ intention to provide counseling, although skill deficits and concern over patient relationships remain notable barriers.